Mengenal Vaksin dan Vaksinasi dalam Pandemi COVID-19 - Aprilia Paramitasari (PROCEEDING UMSURABAYA, 2023)
Abstract The pandemic of COVID-19, which has put a burden on health systems in various parts of the world, requires comprehensive treatment, one of which is vaccination. Vaccination helps the body’s system to produce potent immunity to reduce the risk of infection, morbidity, and mortality due to COVID-19. However, there is a challenge to the existence of this specific vaccine, namely the sars-cov-2 mutation that continues to occur.Keywords: Vaccine, COVID-19, Heterologous Primer-Booster, Cell Memory, Antibody